2014
DOI: 10.1186/1471-2415-14-1
|View full text |Cite
|
Sign up to set email alerts
|

Laser in situ keratomileusis for astigmatism ≤ 0.75 Diopter combined with low myopia: a retrospective data analysis

Abstract: BackgroundThis study examined the refractive and visual outcome of wavefront-optimized laser in situ keratomileusis (LASIK) in eyes with low myopia and compound myopic astigmatism ≤ 0.75 diopter (D).Methods153 eyes from 153 consecutive myopic patients (74 male, 79 female; mean age at surgery 40.4 ± 10.4 years) who had a preoperative refractive cylinder ≤ 0.75 D and a manifest sphere between -0.25 D and -2.75 D, and who had completed 4-month follow-up. Three subgroups defined by the magnitude of preoperative ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 17 publications
4
32
1
Order By: Relevance
“…In terms of vector-based predictability, this study had a tendency to overcorrect the cylinder less than -0.50 D. There were similar results in the previous studies for the LASIK procedure [ 24 , 25 ]. Undercorrection was observed as the cylinder increased, which was inconsistent with the results of MofE, CI and IOS in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…In terms of vector-based predictability, this study had a tendency to overcorrect the cylinder less than -0.50 D. There were similar results in the previous studies for the LASIK procedure [ 24 , 25 ]. Undercorrection was observed as the cylinder increased, which was inconsistent with the results of MofE, CI and IOS in the present study.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have advised caution with full astigmatic correction employing WFO-LASIK in eyes with preoperative cylinder 0.5 D or less. 30,31 Although dividing our data into subgroups demonstrated a trend toward increased angle of error in the eyes with low preoperative astigmatism, this did not reach statistical significance. We also found that both WFO-LASIK and WFG-LASIK did induce de novo astigmatism in several patients.…”
Section: Discussionmentioning
confidence: 55%
“…Cataracts are one of the common causes of visual impairment in diabetic subjects [1, 2]. In patients with diabetes, cataract has an early onset and develops 2 to 5 times more frequently [35].…”
Section: Introductionmentioning
confidence: 99%